We didn't mean to go to sea - "Mowat, Ralph" (Oxford University Press: Oxford, 2000)
The four Walker children never meant to go to sea. They had promised their mother to stay safely in the harbour, and to be home on Friday in time for tea. But there they are in someone else's boat, drifting out to sea in a thick fog. And, then comes the wind and the storm, driving them out even further across the cold North Sea.
Keywords: Sailing ships Juvenile fiction-English